Efektivitas Efektivitas Model Problem Based Learning Berbasis Socio Scientific Issue Terhadap Keterampilan Berpikir Kreatif - Putri Nadlifah Tiara Nita; Nada, Ella Izzatin (LPPM Universitas Negeri Jakarta, 2024)
The importance of mastering the 4C skills—particularly creative thinking—is paramount in the digital era. However, the reality is that the implementation of learning in schools has not yet effectively stimulated creative thinking skills, supported by observation results which show that students' creative thinking skills are relatively low. This research was conducted with the aim of determining the effectiveness of implementing the PBL-SSI model on students' creative thinking skills in green chemistry material. This type of research is quantitative research with a quasy experiment method in the form of a pretest-posttest control group design. The research subjects used were 23 students of SMAN 5 Semarang class X.3 and 28 students of X.4. Determined using a cluster random sampling technique. This research used an independent sample t-test and effect size, the t-test value was <0.001 and the effect size test was 0.708 (medium), indicating that PBL-SSI can stimulate creative thinking skills and there is even an increase in the medium category.